Effects of CYP3A4 Polymorphisms on Drug Addiction Risk Among the Chinese Han Population - Wang, Li; Bai, Mei; Jin, Tianbo; Zheng, Jianwen; Wang, Yuhe; He, Yongjun; Yuan, Dongya; He, Xue (Frontiers in Public Health, 2019)
Background:Cytochrome P450 3A4 (CYP3A4) regulates pharmacokinetic and pharmacodynamic interactions during the process of drug absorption and metabolism, suggesting CYP3A4 plays an important role in drug addiction. However, the association between CYP3A4 polymorphisms and drug addiction risk is still not clear. Methods: This case-control study included 504 drug addicts and 501 healthy controls from Xi'an, China. Four single nucleotide polymorphisms (SNP) in CYP3A4 (rs3735451, rs4646440, rs35564277, and rs4646437) were genotyped by Agena MassARRAY platform. After adjusting by age and gender, we calculated odd ratios (OR) and 95% confidence intervals (CI) by logistic regression to estimate the association between CYP3A4 polymorphisms and drug addiction risk. Results: We found rs4646440 and rs4646437 were associated with decreased risk of drug addiction in codominant (rs4646440: OR = 0.41, 95%CI = 0.19–0.92, p = 0.030; rs4646437: OR = 0.19, 95%CI = 0.04–0.87, p = 0.032) and recessive (rs4646440: OR = 0.41, 95%CI = 0.19–0.91, p = 0.028; rs4646437: OR = 0.20, 95%CI = 0.04–0.90, p = 0.036) models. Rs3735451 and rs4646437 were associated with drug addiction risk in the subgroup of middle-aged people (44 < age ≤ 59) and elderly people (age ≥ 60), individually. For men, rs3735451, rs4646440, and rs4646437 had strong relationship with decreased risk of drug addiction (p < 0.05). The effects of rs3735451 on drug addiction risk were related to drug-using time (p < 0.05). We also observed one block (rs4646440 and rs35564277) in haplotype analysis. Conclusion:CYP3A4 polymorphisms were associated with drug addiction risk among the Chinese Han population.